Innovative proposal of energy scheme based on biogas from digester for producing clean and sustainable electricity, cooling and heating: Proposal and multi-criteria optimization. (October 2022) - Hai, Tao; Dhahad, Hayder A.; Kumar Singh, Pradeep; Almojil, Sattam Fahad; Almohana, Abdulaziz Ibrahim; Alali, Abdulrhman Fahmi; Attia, El-Awady; Shamseldin, Mohamed A.; Ahmed, Ahmed Najat
Highlights: A new system is proposed based on biomass fuel and ejector-based organic flash cycle. The system is investigated from 4E analysis standpoints, and multi-objective optimization is conducted. The ANN and TOPSIS method is used to find the optimum working conditions. Optimization results indicate that, at the optimal point, net power output, cost rate, and pollution becomes 10281 kW, 142.54 $/hr, and 0.53 kg/kWh, respectively. Abstract: It has long since been established that biomass energy may be utilized as a sustainable source to turn chemical energy into electricity, heating and cooling. It has lower emission, higher heat source temperature, available and flexible with many energy systems. In this study the chemical energy of the biomass is used to generate heating, cooling and power, via efficient hybrid ARC and steam rankine cycle based on digester. The system is actually have three main subsystems, the digester and externally fired gas turbine acts as the prime mover and upper cycle of the system. The exit hot gases then are used to heat up an steam rankine cycle the condenser of which is the generator of an ARC. The 3E analysis, and parametric study is conducted. The results indicate that have great effect on system performance. Also the results sighn posted that at its optimal position, the system emits 0.4797 kg of carbon dioxide per kilowatt-hour and has a cost rate of 683 dollars per hour. The most beneficial aspects of the system performance are the pressure ratio of 6.64 and the biomass flow rate of 4.77 kg per second. The system can generate 3375 kW of cooling energy if the temperature of the gas turbine intake is raised to 1450 K and the temperature differential between the pinch point and the gas turbine inlet is raised to 9 °C.